Controls on Timing of Hydrothermal Fluid Flow in South-Central Kansas, North-Central Oklahoma, and the Tri-State Mineral District - Mohammadi, Sahar; Hollenbach, Andrew M.; Goldstein, Robert H.; Möller, Andreas; Burberry, Caroline M. (Midcontinent Geoscience, 2022)
Paleozoic sedimentary rocks in the southern midcontinent of the United States have been affected by multiple events of deformation and fluid flow, resulting in petroleum migration, thermal alteration, Mississippi Valley-type mineralization, and a complex diagenetic history. This record is a hidden history of how cratonal settings respond to tectonic and non-tectonic drivers. The aim of this contribution is to better understand the controls on fluid migration in Paleozoic strata to evaluate whether hydrothermal activity is forced by tectonic or non-tectonic processes. This paper summarizes and vets the distribution of published dates related to thermal events in the southern midcontinent. In addition, we present new U-Pb dates obtained by laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) on calcite cements that were formed from hydrothermal fluids. These are from three samples from the Berexco Wellington KGS 1-32 core in Sumner County, Kansas; an ore sample from the Tri-State Mineral District, Neck City, Missouri; and a core sample from the Blackbird 4-33 well in Osage County, Oklahoma. Previous studies of these calcite samples provided evidence for hydrothermal fluid flow, with one of the Wellington samples possibly recording vertical hydrothermal fluid flow out of the basement. The sample from the Tri-State Mineral District (Missouri) yields a mid-Cretaceous age of 115.6±3.1 Ma. This age falls into the timing of the Sevier Orogeny along the west coast and the development of its foreland basin in the midcontinent. Calcites from the Mississippian interval in the Wellington KGS 1-32 core yield dates of 305±10.5 Ma and 305.1±9.1 Ma. Calcite in Mississippian strata from the Blackbird 4-33 core yields a date of 308.6±2.5 Ma. These dates from Mississippian calcite cements indicate hydrothermal fluid flow in the Late Pennsylvanian that coincides with the timing of the Marathon-Ouachita Orogeny or the Ancestral Rocky Mountains Orogeny. A calcite sample from the Ordovician Arbuckle Group from the Berexco Wellington KGS 1-32 core yielded an age of 5.6±1.6 Ma, coinciding with a time after high elevation uplift of the Rocky Mountains was already far advanced. We propose that this hydrothermal fluid flow may have been associated with increased meteoric recharge and increased regional fluid pressure in a basement aquifer that activated local seismic events far into the continental interior. The distribution of ages of hydrothermal fluid flow confirms a syntectonic driver during the Ouachita Orogeny and Ancestral Rocky Mountains Orogeny deformation. Continuation of hydrothermal fluid flow well into the Permian and tailing off early in the Triassic indicates a post-tectonic driver, where uplifted areas continued to provide the recharge from gravity-driven fluid flow, until the mountains were mostly beveled by the early part of the Triassic. A dearth of Triassic and Jurassic hydrothermal events suggests Gulf of Mexico rifting and extension were less important. Rejuvenation of hydrothermal fluid flow in the Cretaceous and continuing into the Paleogene indicates that elevation and regional flexure from both the Sevier and Laramide events continued to drive hydrothermal fluid flow far from the main sites of mountainous uplift and deformation. Finally, hydrothermal fluid flow associated with more recent uplift of the Rocky Mountains may have been activated by recharge events that pressurized a regional basement aquifer and triggered seismic activity.